2018
DOI: 10.2147/ijn.s153763
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro/vivo drug release and anti-diabetic cardiomyopathy properties of curcumin/PBLG-PEG-PBLG nanoparticles

Abstract: BackgroundThe objective of this study was to survey the therapeutic function of curcumin-encapsulated poly(gamma-benzyl l-glutamate)-poly(ethylene glycol)-poly(gammabenzyl l-glutamate) (PBLG-PEG-PBLG) (P) on diabetic cardiomyopathy (DCM) via cross regulation effect of calcium-sensing receptor (CaSR) and endogenous cystathionine-γ-lyase (CSE)/hydrogen sulfide (H2S).MethodsDiabetic rats were preconditioned with 20 mg/kg curcumin or curcumin/P complex continuously for 8 weeks. The blood and myocardiums were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Curcumin-ZnO (10 mg/kg, for 21 days) nanoparticles were claimed to be more effective than curcumin nanoparticles (50 mg/kg, for 21 days) in diabetes therapy in terms of reduction of blood glucose, improvement in serum insulin, and activation of GLUT2 and glucokinase genes in pancreas and liver of type 2 diabetic rats [191]. Nanocarrier constituted with poly-(γ-benzyl l-glutamate), poly-(ethylene glycol), and poly-(γ-benzyl 1-glutamate) has been shown to improve the bioactivity and water solubility of curcumin [192]. The design of this nanocarrier offered high loading capacity, gradual release, and low cytotoxicity [192].…”
Section: Curcuminmentioning
confidence: 99%
See 3 more Smart Citations
“…Curcumin-ZnO (10 mg/kg, for 21 days) nanoparticles were claimed to be more effective than curcumin nanoparticles (50 mg/kg, for 21 days) in diabetes therapy in terms of reduction of blood glucose, improvement in serum insulin, and activation of GLUT2 and glucokinase genes in pancreas and liver of type 2 diabetic rats [191]. Nanocarrier constituted with poly-(γ-benzyl l-glutamate), poly-(ethylene glycol), and poly-(γ-benzyl 1-glutamate) has been shown to improve the bioactivity and water solubility of curcumin [192]. The design of this nanocarrier offered high loading capacity, gradual release, and low cytotoxicity [192].…”
Section: Curcuminmentioning
confidence: 99%
“…Nanocarrier constituted with poly-(γ-benzyl l-glutamate), poly-(ethylene glycol), and poly-(γ-benzyl 1-glutamate) has been shown to improve the bioactivity and water solubility of curcumin [192]. The design of this nanocarrier offered high loading capacity, gradual release, and low cytotoxicity [192]. Curcumin-encapsulated multi-polymeric nanocarrier achieved better pharmacological effects in cross-regulation of Ca 2+ /calmodulin, calcium-sensing receptor gene and endogenous cystathionine γ-lyase/H 2 S over conventional curcumin formulations in the management of diabetic cardiomyopathy in rats [192].…”
Section: Curcuminmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the effect of the nanoencapsulated polyphenol was done with the polyphenol-void nanocarrier, other bioactives/pharmaceuticals, and also with its free-form. The biological effects and conditions assessed included anti-diabetic and antioxidant activity [63,97,98], diabetic neuropathic pain [99,100], diabetic cardiomyopathy [101,102], inflammation [103][104][105], and cataract in a diabetic rat model [106]. It was reported that nanoencapsulated curcumin produced anti-diabetic effects by increasing the number of insulin positive cells and the gene expression of insulin, alleviating STZ-induced β-cell damage and increasing the upregulation of the transcription factors pancreatic and duodenal homeobox 1 (Pdx-1), which play a critical role in pancreatic development, and NKx6.1 which is required for the development of β-cells [97,98].…”
Section: Diarylheptanoidmentioning
confidence: 99%